2017
DOI: 10.1161/hypertensionaha.117.09063
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Resistance to Angiotensin II–Induced Hypertension in the Jackson Laboratory Recombination-Activating Gene Null Mouse on the C57BL/6J Background

Abstract: Resistance to angiotensin II (Ang II)-induced hypertension in T-cell deficient male mice with a targeted mutation in the recombination activating gene-1 (Rag1) on the C57BL/6J background (B6.Rag1−/−-M), which was reported by five independent laboratories including ours prior to 2015, has been lost. In mice purchased from Jackson Laboratory in 2015 and 2016, the time course and magnitude increase in mean arterial pressure (MAP) induced by two weeks of Ang II infusion at 490 ng/kg/min was identical between B6.Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Inhibition of ANG II-induced hypertension in Rag1Ϫ/Ϫ mice have been confirmed by several distinct institutions (432,829,1074,1095). One laboratory, however, could not confirm their finding (432) when the mice were repurchased recently (431), suggesting that spontaneous mutations might be occurring in the inbred strain. Distinct expression levels of glomerular ANG II receptors were suggested to explain the difference according to binding studies.…”
Section: Limitations and Pitfalls In Ang II Signaling Researchmentioning
confidence: 99%
“…Inhibition of ANG II-induced hypertension in Rag1Ϫ/Ϫ mice have been confirmed by several distinct institutions (432,829,1074,1095). One laboratory, however, could not confirm their finding (432) when the mice were repurchased recently (431), suggesting that spontaneous mutations might be occurring in the inbred strain. Distinct expression levels of glomerular ANG II receptors were suggested to explain the difference according to binding studies.…”
Section: Limitations and Pitfalls In Ang II Signaling Researchmentioning
confidence: 99%
“…81 Just recently, the importance of T cells in hypertension, as recruited to the PVAT, in both Ang-II and DOCA-salt hypertension in mice, was called into question with the inability of multiple labs across the country to reproduce the previously observed protection of the Rag1 mice (lack T and B cells) from Ang-II-induced hypertension. 82 In dysfunctional PVAT (e.g., hypertension), immune cell infiltration becomes more prominent. Infiltrating cells include macrophages, memory T cells, IL-10-producing FoxP3 + T regulatory cells, natural killer cells, and granulocytes.…”
Section: Immune Cell Infiltration and Pvatmentioning
confidence: 99%
“…These provocative findings(2,(5)(6)(7), which challenge those that initially demonstrated blunted hypertension responses in Rag1-deficient mice(3), raise a number of important questions. Firstly, why does the same Rag1 immunodeficient mouse model yield diametrically opposed results?Secondly is the Rag1 KO animal the most appropriate pre-clinical model to study immune responses in hypertension?…”
mentioning
confidence: 93%
“…Ji et al also failed to show that Rag1 KO mice are protected from Ang II-induced hypertension (6) and Uchida et al demonstrated that total lymphocyte deficiency in Rag1-/-mice had no effect on systolic blood pressure prior to and during Ang II infusion (2). Moreover, in a model of arterial injury, immune deficiency in Rag1 KO mice was associated with augmented, rather than reduced, neointima formation, effects that were attenuated by CD8 T cells, but not by CD4 T cells (7).…”
mentioning
confidence: 99%